আবহমান বাংলা - ইসলাম, মুস্তাফা নূরউল, ১৯২৭- (ঢাকা : মোহাম্মদ আমিনুল হক, 1993)
On the cultural heritage of Bangladesh from ancient times to modern period; collection of contributed articles previously published in the Sundaram, a quarterly journal from Dhaka, Bangladesh.
In Bengali.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত।
Donated by Rebecca Dipa Khan
Keywords: Bangladesh -- Civilization